Bid'a in the Perspective of Islamic Theology and Law - Musawar Musawar (Ulumuna, 2019)
Bid’a, literally translated as religious heresy and innovation, has become a topic of controversy amongst Muslims. There are Prophetic traditions that address bid’a in the most critical term, declaring its perpetrators of misguided persons threatened by hellfire. This paper critically examines the notion of bid’a and conceptually analyzes it from the perspectives of Islamic theology and law. Based on textual analysis of this term as this is found in some Prophetic traditions and their interpretation by Muslim scholars, this paper shows that the meaning of bid’a covers various aspects of Islam, including theology and law. Muslims scholars understand the hadith on bid’a literally and contend that all innovations are misleading. Other scholars, however, suggest that based on their critical examination of the term from linguistic, contextual and practical aspects, not all bid’a are misguided. These scholars tend to comprehend bid’a from the perspective of Islam law rather than theology. According to Islamic law, human actions fall into five legal categories: compulsory, recommended, neutral, reprehensible and forbidden. Bid’a must be put into this perspective. In other words, not all new things and innovation are forbidden because they can be categorised as neutral or recommended, depending on the relevant legal considerations.